Structural Aspects of the Labor Markets of Five OECD Countries - Geert Ridder; Niels de Visser; Gerard van den Berg (Tinbergen Institute, 1997)
The simplest equilibrium search models depend on a few parameters that determine the joint distribution of unemployment spells, job spells, and wages. In this study we use aggregate data to estimate these key parameters for five OECD countries: (West-)Germany, The Netherlands, France, the United Kingdom and the USA. We show that in the simple model only information on the marginal distribution of wages and the marginal distributions of unemployment and job spells is needed to estimate the structural parameters. Thus, the methodological contribution of this paper is the demonstration that the model can be calibrated from readily available aggregate data, and that panel data on individuals are not necessary. Our estimation method provides a direct link between types of information and parameters. We show that data on job durations allow us to estimate an index of the search frictions, without the need to estimate the other parameters simultaneously. The parameters, the arrival rate of wage offers, the rate of job destruction, the average productivity of jobs, and the variation of job productivities are of interest in their own right. We also use the parameter estimates to obtain estimates of structuralunemployment due to wage floors, of the average level of monopsony power in the economy, and to make a decomposition of wage variation into variation due to productive differences between jobs and variation due to search frictions.
Keywords: 330